2004
DOI: 10.1080/03009740310004702
|View full text |Cite
|
Sign up to set email alerts
|

Arthralgia and digital clubbing in a child: hypertrophic osteoarthropathy with inflammatory pseudotumour of the lung

Abstract: Arthralgia in childhood is an unspecific symptom. One rare cause of arthralgia is hypertrophic osteoarthropathy associated with digital clubbing. We present a child where hypertrophic osteoarthropathy led to the rare diagnosis of an inflammatory pseudotumour of the lung. In a 12-year-old girl with arthralgia and digital clubbing, a chest radiograph disclosed a large round mass in the right upper lobe, and the following chest computed tomography scan showed a large solid homogenous, round, well marginated lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Including our patient, in nine cases the children presented with variable degree of anemia. They also showed laboratory findings of chronic inflammation such as leukocytosis, hypergammaglobulinemia, elevated platelet count, increase of erythrocyte sedimentation rate, and C-reactive protein ( 12 , 14 , 15 , 17 , 18 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including our patient, in nine cases the children presented with variable degree of anemia. They also showed laboratory findings of chronic inflammation such as leukocytosis, hypergammaglobulinemia, elevated platelet count, increase of erythrocyte sedimentation rate, and C-reactive protein ( 12 , 14 , 15 , 17 , 18 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The histological assessment is essential to rule out pseudo-lymphomas, malignant lymphomas, lymphoid hyperplasia and sarcomas such as leiomyosarcoma, fibrosarcoma, rhabdomyosarcoma, myxoid sarcoma, malignant fibrous histiocytoma, and gastrointestinal stromal tumor ( 12 , 14 , 15 , 17 , 18 , 24 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nail clubbing and hypertropic osteoarthropathy has also been reported. 20 Because of the lack of literature on IPT involving only the pleura we will have to extrapolate the information obtained from the cases with pleural involvement from the pulmonary IPT. Exudative pleural effusion rich in cellular elements with pleuritic chest pain may be the most common presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, presentation with finger clubbing and joint problems has been documented previously. Pichler et al reported a case of a 12-year-old girl with arthralgia and finger clubbing in whom a chest radiograph revealed a lung tumour 12 . The tumour was resected and found to be an inflammatory myofibroblastic tumour; following resection, the patient's arthralgia disappeared.…”
Section: Discussionmentioning
confidence: 99%